Americanization and the role of cinema in shaping early Soviet culture - Levitina, Marina L. (Trinity College (Dublin, Ireland). Department of Russian & Slavonic Studies, 2011)
This dissertation argues that the Americanization discourse of the 1920s was one of the key sources for the project of creating the New Soviet Man and Woman, and that Soviet cinema of the 1920s and 1930s played an important role in this project, by creating a new type of Soviet cinematic hero(ine) and promoting the positive human traits that were perceived as innately American - such as energy, optimism, physical fitness, efficiency, technological skills, resourcefulness, and the frontiersman's selfreliance, - even if not directly acknowledging the connection with American culture.
Keywords: Russian & Slavonic Studies, Ph.D.; Ph.D. Trinity College Dublin.